Analisis Visual Clutter Antarmuka Aplikasi Belanja Online Menggunakan Metode System Usability Scale - Anak Agung Yoga Aditya Putra; Cokorda Pramartha (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
This study investigates the phenomenon of visual clutter in mobile online shopping applications, a growing concern given the rapid expansion of the e-commerce industry and increasing reliance on mobile devices for shopping activities. Visual clutter, characterized by an overly dense, unfocused, or excessive display, can disrupt user interaction, heighten cognitive load, and diminish the effectiveness of visual search. The research specifically analyzes the degree of visual clutter within a selected online shopping application interface, representing a mobile e-commerce platform. The System Usability Scale (SUS) method was employed to quantitatively assess user perceptions of the application's usability. The findings are expected to offer valuable insights for developing more structured and user-friendly online shopping application interfaces.